2014
DOI: 10.3389/fmicb.2014.00619
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen gas flushing can be bactericidal: the temperature-dependent destiny of Bacillus weihenstephanensis KBAB4 under a pure N2 atmosphere

Abstract: Gram-negative Pseudomonas and Gram-positive Bacillus are the most common spoilage bacteria in raw and pasteurized milk, respectively. In previous studies, nitrogen (N2) gas flushing treatments of raw and pasteurized milk at cold chain-temperatures inhibited bacterial spoilage and highlighted different susceptibilities to the N2 treatment with the exclusion of certain bacterial types. Here, we investigated the effects of pure N2 gas flushing on representative strains of these genera grown in mono- or co-culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…No bactericidal type of action was noticed with N in this study, in contrast to HT. However, that N 2 gas flushing does not exert any bactericidal action is not that straightforward considering recent observations showing that N 2 gas flushing can act as a bactericidal agent for Bacillus weihenstephanensis , a Gram-positive representative found in pasteurized milk (Lechner et al, 1998 ; Munsch-Alatossava et al, 2013 ), as a majority of cells were considerably damaged based on electron microscopic observations following the flushing treatment (Munsch-Alatossava and Alatossava, 2014 ). Most probably, our plating conditions, which did not specifically target Bacillus types of Gram-positive bacteria, together with the fact that Bacillus is usually present in low numbers in raw milk, prevented the detection of any bactericidal type of action in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No bactericidal type of action was noticed with N in this study, in contrast to HT. However, that N 2 gas flushing does not exert any bactericidal action is not that straightforward considering recent observations showing that N 2 gas flushing can act as a bactericidal agent for Bacillus weihenstephanensis , a Gram-positive representative found in pasteurized milk (Lechner et al, 1998 ; Munsch-Alatossava et al, 2013 ), as a majority of cells were considerably damaged based on electron microscopic observations following the flushing treatment (Munsch-Alatossava and Alatossava, 2014 ). Most probably, our plating conditions, which did not specifically target Bacillus types of Gram-positive bacteria, together with the fact that Bacillus is usually present in low numbers in raw milk, prevented the detection of any bactericidal type of action in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The factor “time” seems to play also a crucial role when considering the mode of action of N 2 gas: for raw milk samples stored at 6°C, it appeared that phospholipase producers were excluded in a sample-dependent manner under the N 2 flushing treatment after 3, 7, or 11 d (Munsch-Alatossava et al, 2010b ). Additionally, many days were necessary to record a bactericidal type of action on Bacillus weihenstephanensis under the same continuous N 2 gas flushing (Munsch-Alatossava and Alatossava, 2014 ), which altogether suggests that unlike HT (which exerts rather rapid action), the action of N 2 gas flushing seems to be inscribed in time.…”
Section: Discussionmentioning
confidence: 99%
“…(3) monoculture of C1, N 2 -flushed; and (4) monoculture of C1, as a control. The bacterial counts were detailed in a previous study (Munsch -Alatossava and Alatossava, 2014). (B) The raw milk isolate J8 was grown in BHI broth for 10 days at 6 • C. J8/C accounts for the control (ambient air), whereas J8/N corresponds to the N 2 -flushed culture.…”
Section: Effects Referencesmentioning
confidence: 99%
“…Dechemi et al (2005) observed minor changes in the pH of raw milk under 100% N 2 ; however, the same study reported that the 100% N 2atmosphere showed poor inhibition of psychrotrophs, and their proteolytic and lipolytic activities. N 2 gas-flushing of raw milk, when applied to an "open system, " revealed the following advantages: bacterial development was significantly inhibited at laboratory and pilot-plant scales, while bacterial diversity was better preserved during cold-storage; the treatment was mostly of equal efficiency compared to the activated lactoperoxidase system (for treating raw milk stored at 15 or 25 • C); the same treatment targeted Pseudomonas spp., triggered a bactericidal type of effect toward Bacillus weihenstephanensis, while showing a significant protective effect on antioxidant compounds, alleviation of phospholipolysis, and reduction in the risk of antibiotic resistance disseminating in raw milk (Munsch- Alatossava et al, 2010aAlatossava et al, ,c, 2016Alatossava et al, , 2018Munsch-Alatossava and Alatossava, 2014;Gschwendtner et al, 2016;Gursoy et al, 2017;Alatossava and Munsch-Alatossava, 2018).…”
Section: Introductionmentioning
confidence: 99%